Carbon Conversion Using High Voltage Plasma Method Based on Mangrove Wood Charcoal - Aldi, Robi; Feranita, Feranita; Murdiya, Fri; Safrianti, Ery; Sari, Linna Oktaviana (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2023)
This study investigates the conversion of mangrove wood charcoal into graphene using high voltage plasma technology through arc discharge. The experiment involves heating carbon with high voltage plasma generated from rod and plate electrodes. The variables examined are the electrode distance and carbon treatment time. The results demonstrate the successful conversion of mangrove wood charcoal into graphene. The generated plasma is influenced by the electrode distance, with a 1 cm gap producing stronger bluish-orange plasma. Varying the treatment time also affects the graphene yield, with a 3-minute treatment generating more graphene compared to 2 minutes, and 2 minutes yielding more graphene than 1 minute. XRD analysis reveals characteristic peak shifts indicative of graphene presence. SEM analysis confirms the graphene structure with porous features and sub-micrometer sizes. SEM images and diameter data further validate the successful conversion of carbon into graphene. These findings provide a foundation for the development of high voltage plasma-based production of graphene from mangrove wood charcoal. The utilization of a 10kV Neon Power Supply transformer enables the generation of high voltage plasma for the carbon-to-graphene conversion process. The electrode distance in the transformer plays a crucial role, as greater distances result in higher voltages, while shorter distances lead to lower voltages. This research significantly contributes to expanding the knowledge and application of graphene in various scientific and engineering fields. Moreover, the understanding of how electrode distance affects the generated voltage using a Neon Power Supply transformer is an important finding for optimizing the performance of this type of transformer.